The development of student teachers' sense of professional agency in the classroom during teacher education. (2nd July 2020) - Heikonen, Lauri; Pietarinen, Janne; Toom, Auli; Soini, Tiina; Pyhältö, Kirsi
ABSTRACT: Teacher education needs to facilitate the development of student teachers' capacity for active and skilful learning in classroom interaction, referred to as sense of professional agency in the classroom. It consists of motivation to learn, self-efficacy beliefs about learning, and strategies promoting one's own and pupils' learning in the classroom. However, not much is known about how student teachers' sense of professional agency in the classroom develops during teacher education. This longitudinal study investigated the interrelations between the components of Finnish student teachers' (N = 268) sense of professional agency in the classroom during teacher education. Structural equation modelling was used to analyse the data that was collected annually during the bachelor's degree phase of primary school teacher education. The results showed that the construction of student teachers' sense of professional agency in the classroom was based on being able to interpret and analyse classroom interaction and became more strongly related to their abilities to use peers, more experienced teachers, and pupils as resources in constructing supportive collaborative learning environments and developing functional engaging teaching methods. The findings suggest that professional agency in the classroom is a functional integrative concept for investigating student teacher learning and developing teacher education.